Analisa Penerapan Akuntansi Pada Pembiayaan Gadai Emas Syariah Di Bank Syariah Indonesia Cabang KFO POS Sesetan - wahyuni romadani; Lucy Sri Musmini (Vokasi : Jurnal Riset Akuntansi, 2025)
Sharia pawn financing is the physical guarantee/right of control over valuables in the form of gold (jjewelry or gold) to a bank as collateral for the financing (qard) received. Sharia gold pawn financing requires a comprehensive accounting framework that can produce accourate accounting measurements. The researcher chose Bank Syariah Indonesia KFO POS Sesetan because one of its branches specifically serves sharia gold pawn. This type research is descriptive research with qualitative methods. The research used qualitative methods with a case study approach. The data collected in this research is qualitative data, primary and secondary data. The data analysis used is descriptive analysis aimed at providing a description of the research subject. Rahn or pawning is financing provided by sharia bank to customer with gold collateral. Where the gold pawning financing uses 3 qard, rahn, and ijarah. The legal basis of pawning (rahn) is based on DSN Fatwa No. 25/DSN-MUI/III/2002 andd DSN Fatwa No. 26/DSN-MUI/III/2002. This financing exist because of the large number of customers who need funds for expenser or surges. The implementation or accounting practices that have been carried out are in accordance with PSAK 107. In presenting the financial statements of Bank Syariah Indonesia KFO POS Sesetan branch, have compiled and presented them in accourdance with PSAK 107, in the financial statements the bank hass disclosed significant information regarding the total payment of sharia gold pawn financing and presented sharia gold pawn financing in the same account as the pawn prodcuct (ijarah).